Pengaruh Employer Branding, Reputasi Perusahaan, Informasi Sosial Media dan Corporate Social Responsibility terhadap Niat Melamar Pekerjaan Generasi Milenial dan Generasi Z - Kusdiyanto; Ishbah, Faliqul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the influence of employer branding, corporate reputation, social media information, and corporate social responsibility on the intention to apply for jobs among millennials and Generation Z in Surakarta. The approach used in this study is quantitative, employing a survey method with questionnaires distributed to 100 respondents who meet the criteria. Data analysis was conducted using the Structural Equation Model (SEM) with Partial Least Square (PLS). The results show that employer branding, corporate reputation, social media information, and corporate social responsibility have a positive and significant influence on the intention to apply for jobs. Employer branding and corporate reputation enhance the company's attractiveness to potential job applicants. Information disseminated through social media also plays a crucial role in attracting application interest. Additionally, corporate social responsibility conducted by the company positively impacts the perception of potential employees. This study implies that companies need to pay attention to branding strategies, maintain their reputation, utilize social media, and enhance social responsibility to attract job application interest from millennials and Generation Z.